Gene expression patterns and related enzymatic activities of detoxification and oxidative stress systems in zebrafish larvae exposed to the 2, 4-dichlorophenoxyacetic acid herbicide. (June 2019) - Gaaied, Sonia; Oliveira, Miguel; Le Bihanic, Florane; Cachot, Jérôme; Banni, Mohamed
Abstract: The present study aims to assess the effects of 2, 4-D herbicide on biotransformation and oxidative stress status of zebrafish larvae. Animals were exposed to a range of sublethal concentrations (0.02–0.8 mg/L) and biomarkers at transcriptomic level and biochemical level were assessed. Chemical analysis with showed that the bioaccumulation of 2, 4-D in 96 hpf zebrafish larvae were increased in a concentration-dependent manner. This herbicide induced significant effects at both gene expression and enzymatic activities levels after at 96 hpf. Results of mRNA expression showed a differential transcription regulation with all target genes depending on the tested concentrations. The mRNA level of gsr and cyp1a were up regulated at the highest dose of herbicide (0.8 mg/L). The gene expression of gstp1 showed an up regulation at lower dose (0.02 mg/L) and a down regulation at the highest dose (0.8 mg/L) of 2, 4-D. A significant induction of EROD activity and inhibition of GST activity were noted in groups exposed to 0.8 mg/L of 2, 4-D. Considering the antioxidant defenses, the activity of CAT was increased in larvae exposed to 0.8 mg/L of herbicide and GPx activity was induced at lower doses of 2, 4-D (0.02 and 0.051 mg/L). Moreover, peroxidative damage, assessed as MDA content, was markedly increased in larvae exposed to high 2, 4-D concentration. Overall, the present study data indicate that bioaccumulation of 2, 4-D in 96 hpf zebrafish larvae and alterations in detoxification and oxidative stress related parameters, likely associated with ROS production, which may endanger the embryo-larval stages development of fish. Graphical abstract: Image 1 Highlights: Sublethal exposure to 2, 4-D herbicide contribute to oxidative stress in zebrafish larvae. 2, 4-D alters gene expression of detoxification and oxidative stress enzyme in zebrafish larvae. 2, 4-D modulate detoxification and oxidative stress enzyme activities in zebrafish larvae. 2, 4-D enhances MDA level in 96 hpf zebrafish larvae.